2021
DOI: 10.1073/pnas.2020833118
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of fishing-associated selection varies with population density

Abstract: Fisheries induce one of the strongest anthropogenic selective pressures on natural populations, but the genetic effects of fishing remain unclear. Crucially, we lack knowledge of how capture-associated selection and its interaction with reductions in population density caused by fishing can potentially shift which genes are under selection. Using experimental fish reared at two densities and repeatedly harvested by simulated trawling, we show consistent phenotypic selection on growth, metabolism, and social be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Our results showed that intensive size-selective mortality leads to complex, multivariate, and asymmetric responses that vary with the type of size-selection operating on fish, a pattern also reported in other recent studies (Claireaux et al 2018;Le Rouzic et al 2020;Renneville et al 2020;Crespel et al 2021b;Bartuseviciute et al 2022). However, we can conclude that size-selective mortality left an evolutionary impact on the ontogentic changes of shoal cohesion and also impacted the physiological basis of behavior.…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that intensive size-selective mortality leads to complex, multivariate, and asymmetric responses that vary with the type of size-selection operating on fish, a pattern also reported in other recent studies (Claireaux et al 2018;Le Rouzic et al 2020;Renneville et al 2020;Crespel et al 2021b;Bartuseviciute et al 2022). However, we can conclude that size-selective mortality left an evolutionary impact on the ontogentic changes of shoal cohesion and also impacted the physiological basis of behavior.…”
Section: Discussionsupporting
confidence: 87%
“…This offers support for our results and indicates that stopping selection might not have hampered feeding behaviour. That said, it is possible that the observed variations among selection lines are due to other factors like density (Bouffet‐Halle et al 2021 ; Crespel et al 2021a , b ) and genetic drift (Therkildsen et al 2019 ). A recent study in medaka showed that life-history divergence may not be caused by direct harvest selection but by natural density-dependent selection for a larger body-size (Bouffet‐Halle et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of evolution in an exploited population depends on the size groups that are removed by fishing, which are ultimately determined by the size selectivity of gears and the intensity of harvest (Therkildsen et al, 2019;Crespel et al, 2021). In order to control the negative effects of FIE, low fishing mortalities have been suggested as a general remedy (Heino, 1998;Law, 2000;Laugen et al, 2014).…”
Section: Management Implications For Japanese Spanish Mackerel In Res...mentioning
confidence: 99%